2019
DOI: 10.1365/s41056-019-00028-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk measures for direct real estate investments with non-normal or unknown return distributions

Abstract: The volatility of returns is probably the most widely used risk measure for real estate. This is rather surprising since a number of studies have cast doubts on the view that volatility can capture the manifold risks attached to properties and corresponds to the risk attitude of investors. A central issue in this discussion is the statistical properties of real estate returns-in contrast to neoclassical capital market theory they are mostly non-normal and often unknown, which render many statistical measures u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Moreover, the financial dimensions of the investment, encompassing acquisition expenses, potential returns, and associated risks, significantly influence the land's worth [41][42][43] . Speculators engage in financial assessments, evaluating cash flow forecasts, prospective capital appreciation, and the timeframe for realizing investment returns [40,44] .…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the financial dimensions of the investment, encompassing acquisition expenses, potential returns, and associated risks, significantly influence the land's worth [41][42][43] . Speculators engage in financial assessments, evaluating cash flow forecasts, prospective capital appreciation, and the timeframe for realizing investment returns [40,44] .…”
Section: Related Workmentioning
confidence: 99%
“…There is some consensus in financial theory that risk generally expresses the change in the return on the capital invested Δi C , which can be measured in different ways, such as volatility or maximum drawdown. This shall not be explored further here, for a detailed discussion of real estate risk measures see Lausberg et al (2020). Instead, it shall be shown that using the yield is also problematic.…”
Section: Indicators Of Riskmentioning
confidence: 99%
“…Size, location, specifications, supply, interest rate, and availability of utilities such as swimming pools are all variables that influence land costs. Many variables influence land pricing, including location, neighbourhood, size, specifications, services supplied, market scenario, and so on (4). People nowadays require homes and land in order to secure their future as a long-term investment for their own usage and capital in the globe.…”
Section: Introductionmentioning
confidence: 99%